Cervical Spine Injuries and Maxillofacial Trauma: A Systematic Review - Feras AlMofreh, DDS; Sami AlOtaibi; Mohamed Jaber; Khaled Bishawi, DDS; Ahmed AlShanably, DDS; Faris AlMutairi (Elsevier, 2021)
Objectives: Identify specific maxillofacial trauma patterns associated with cervical spine injuries. Methods: The protocol was developed according to (PRISMA-P) and was admitted to PROSPERO under accreditation code #CRD42020177816. Furthermore, the reporting of the present SR was conducted based on the PRISMA checklist. Results: Of the 1,407,750 patients recorded, a total of 115,997 patients (12.13%) had MFF with an associated CSI with a gender proportion (M:F) of 3.63:1 respectively. Motor vehicle accident was the most common cause of the combined Maxillofacial Trauma (MFT) and CSI. The most common CSI location was at the C2, followed by the C5 cervical spines. The most common location of a maxillofacial fracture resulting in a CSI was the mandible. Conclusion: The incidence of the association of CSIs with MFT has been low (12.13%). Nevertheless, in cases of an isolated mandibular trauma due to a severe blow presenting with a low Glasgow Coma Scale, maxillofacial surgeons should be at a high alert of an associated CSI.